Time-Resolved scRNA-Seq Tracks the Adaptation of a Sensitive MCL Cell Line to Ibrutinib Treatment - Fuhr, Viktoria (Int J Mol Sci, 2021)
Since the approval of ibrutinib for relapsed/refractory mantle cell lymphoma (MCL), the treatment of this rare mature B-cell neoplasm has taken a great leap forward. Despite promising efficacy of the Bruton tyrosine kinase inhibitor, resistance arises inevitably and the underlying mechanisms remain to be elucidated. Here, we aimed to decipher the response of a sensitive MCL cell line treated with ibrutinib using time-resolved single-cell RNA sequencing. The analysis uncovered five subpopulations and their individual responses to the treatment. The effects on the B cell receptor pathway, cell cycle, surface antigen expression, and metabolism were revealed by the computational analysis and were validated by molecular biological methods. The observed upregulation of B cell receptor signaling, crosstalk with the microenvironment, upregulation of CD52, and metabolic reprogramming towards dependence on oxidative phosphorylation favor resistance to ibrutinib treatment. Targeting these cellular responses provide new therapy options in MCL.